If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -2 = -8 + 3x Reorder the terms: -2 + 2x = -8 + 3x Solving -2 + 2x = -8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + 2x + -3x = -8 + 3x + -3x Combine like terms: 2x + -3x = -1x -2 + -1x = -8 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + -1x = -8 + 0 -2 + -1x = -8 Add '2' to each side of the equation. -2 + 2 + -1x = -8 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = -8 + 2 -1x = -8 + 2 Combine like terms: -8 + 2 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 5(y-3)-3(y-2)=8 | | (3)/(8)x-(1)/(4)=2 | | 40-x=12x | | 48=4n/7+n | | -8(-3)(-3)= | | y=-4(18+-7y)+18 | | 4z-11-z+2=0 | | -2x(5x-8)=6x | | 8a+3=3 | | 9x-1=125 | | 1/8(5x+4)=3.4 | | (1)/(8)x=(1)/(2) | | (x-5)/(3*x)+(6/2*x+1)=0 | | (8x+9)(7x^2+9x+9)= | | (5)/(6)x=-15 | | 5t-t-7=3t-4 | | 3/4(-4y-8x+4z) | | 6(2q+1)=9q-12 | | (7x^2-8x-10)(x-9)= | | 5x=4x-3/4 | | 3/5*10x | | 8.4o-6.8=14.3+6.3o | | 5+4y=2y-13 | | 10m+16n=140 | | -2x^4y^2= | | -27x-9y=18 | | N^2+5n-266=0 | | 2(3x-2)-5x=5-2x | | X-(45)=16 | | (-2x^4y^2)= | | 73-5x=40x+23 | | 0=x^5+4x^4+4x^3 |